(untitled) (Eurasian Journal of Ecology, 2016)
Ecological situation is stay with important environmental pollution. Reglementations of live-stock in the polluted area is not clear. Some studies were achieved to measure impact of heavy met-als, organic polutants on different farm animals. Globally information about impact of heavy metals and/or organic pollutants on livestock products is not enough. Especially recent data is very few and inludes not all livestock products. The available data shown in the present paper, cannot explaining of the mechanisms of exposure and of detoxification. The assessment of contamination risk is not yet known in the situation of Kazakhstan.